Evaluation of genetic resistance to Salmonella Pullorum in three chicken lines. (23rd December 2017) - Li, Xinghua; Nie, Changsheng; Zhang, Zebin; Wang, Qiong; Shao, Pingping; Zhao, Qingna; Chen, Yu; Wang, Dehe; Li, Yajie; Jiao, Wenjie; Li, Lixia; Qin, Sudi; et al.
Abstract: Resistance to diseases varies considerably among populations of the same species and can be ascribed to both genetic and environmental factors. Salmonella Pullorum (SP) is responsible for significant losses in the poultry industry, especially in developing countries. To better understand SP resistance in chicken populations with different genetic backgrounds, we orally challenged 3 chicken lines with SP—a highly selected commercial breed (Rhode Island Red, RIR), a local Chinese chicken (Beijing You, BY), and a synthetic layer line (dwarf, DW)—at 4 d of age. Two traits related to SP resistance, survival, and bacterial carriage in the spleen were evaluated after infection. Survival rates were recorded up to 40 d of age when all chickens still alive were killed to verify the presence of SP in the spleen to determine carrier state. Mortalities for RIR, BY, and DW chicks were 25.1%, 8.3%, and 22.7%, respectively, and the corresponding carrier-states in the spleens were 17.9%, 0.6%, and 15.8%. Survival and carrier-state heritabilities were estimated using an animal threshold model. Survival heritability was 0.197, 0.091, and 0.167 in RIR, BY, and DW populations, respectively, and the heritabilities of carrier state for DW and RIR were 0.32 and 0.16, respectively. This is the first time that the heritability of the SP carrier state has been evaluated in chickens. Our study provides experimental evidence that chickens with various genetic background exhibited significantly different SP-resistant activities and heritabilities. These results may be useful for selecting lines with better disease resistance.